Intracranial stenting with the Neuroform Atlas Stent for symptomatic intracranial atherosclerotic stenosis: a bi-center retrospective analysis including stroke recurrence nomogram - Peng, Weicheng; Ma, Haiyang; Xiang, Xinli; Zhao, Rui; Lv, Meng; Xu, Sheng; Jiang, Yuhua; Hu, Zhiqiang; Guan, Feng (Frontiers in Neurology, 2025)
BackgroundIntracranial stenting with the Neuroform Atlas Stent is an emerging option for patients with symptomatic intracranial atherosclerotic stenosis (sICAS) who do not respond to intensive medical treatment. However, the efficacy, safety, and risk factors associated with postoperative stroke recurrence remain controversial.MethodsA total of 326 consecutive patients with sICAS treated with intracranial stenting using the Neuroform Atlas Stent were retrospectively analyzed to evaluate the efficacy and safety of the procedure. Patients were randomly assigned to a training set and a validation set in a 7:3 ratio. Significant variables in the univariate logistic analyses were included in the final multivariate logistic regression analyses in the training set. Subsequently, we developed a predictive nomogram for sICAS treated with a Neuroform Atlas Stent to predict the likelihood of stroke recurrence at 6 months.ResultsThe overall mean stenosis rate of the target artery was 88.85% ± 6.53% before the stenting (T0), 47.58% ± 9.94% at the end of the procedure (T1), and 40.21% ± 7.77% at the 6-month follow-up (T2). The stenosis rate was statistically significant between T0 and T1 (p < 0.01) and between T0 and T2 (p < 0.01). At 6 months postoperatively, 36 patients had a stroke recurrence linked to the target artery. Diabetes, acute ischemic stroke (AIS), plaque burden on vessel wall MRI, enhancement ratio on vessel wall MRI, and stenosis (T1) were independent predictors of stroke recurrence. A predictive nomogram was developed, showing strong predictive capability with the area under the curve of 0.933 for the training set and 0.949 for the validation set.ConclusionIntracranial stenting with the Neuroform Atlas Stent is a potentially safe and effective treatment for sICAS. Risk factors for recurrent stroke post-procedure include diabetes, current smoker, current drinker, AIS, plaque burden, enhancement ratio, and stenosis (T1).